Спогади Надії Суровцової як феномен української мемуаристики - Біличенко, Ольга; Belichenko, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
Розглянуто особливості мемуаристики Надії Суровцової як одного із пер- ших досвідів української автобіографічної жіночої літератури. Зроблено спробу визначити місце спогадів у творчому доробку письменниці та українській авто- біографічній прозі.The features of memorialist of Nadia Surovtsova are considered as one of the first experiences of Ukrainian autobiographic female literature. An author tries to define the place of memories in creative work of authoress and Ukrainian autobiographic prose. Autobiographic prose of the authoress is presented as the unique example of Ukrainian memoirs. N. Surovtsova’s memories demand detailed study, proper realization of literary criticism. Nowadays there exists urgent necessity in generalized study of “Memories” of the authoress as all-sufficient part of cultural process. Memories of N. Surovtsova are the conclusion of her experience, knowledge source of history lessons for contemporaries. At the same time, “Memories” are perceived as modern work. Problems raised in them are still relevant nowadays because they interpret events of XX century and culture in general.
Memorie of Nadia Surovtsova as Fenomen Ukrainian Memorialistic
Keywords: мемуаристика; автобіографічна проза; жіноча література; memoirs; autobiographic prose; female literature